Golden Jubilee of BCPS: Missed Opportunities & Star Gazing - Yunus, Emran Bin (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Abstract not available J Bangladesh Coll Phys Surg 2022; 40: 110-112